DETERMINANTS OF THE FORMATION OF CHINA'S SMART ECONOMY - Liudmyla Tsymbal; Tymur Natsvlishvili (Izdevnieciba "Baltija Publishing", 2023)
The development of China's smart economy has been heavily influenced by the government's strategic policies and investments in key technologies. One of the key technologies driving China's smart economy is the Internet of Things (IoT), which involves connecting machines, devices and sensors to the Internet for real-time data collection and analysis. This enables the optimisation of production processes and improved efficiency in industries such as manufacturing. The Chinese government has actively promoted the adoption of IoT technologies in manufacturing through policies such as the Made in China 2025 plan and the Internet Plus strategy. Another essential technology for China's smart economy is big data, which enables intelligent decision-making in various industries such as finance, healthcare and transportation. The government has encouraged the development of big data infrastructure, including data centres and cloud computing, to support the growth of the industry. Initiatives such as the National Big Data Comprehensive Pilot Zone have been established to promote the development of the big data industry. Artificial intelligence (AI) is also a key technology for China's smart economy, and the government has made significant investments in AI research and development. In 2017, China announced its plan to become a world leader in AI by 2030, with the aim of building a domestic AI industry worth $150 billion. The government has launched initiatives, such as the AI Development Plan, to build an AI ecosystem and promote the integration of AI with traditional industries. Robotics is another critical technology for China's smart economy, particularly in manufacturing. The government has encouraged the use of robots in manufacturing through tax incentives and subsidies, making China the world's largest market for industrial robots. The government aims to further develop the robotics industry to meet the needs of China's smart economy. In conclusion, China's smart economy is driven by strategic policies and investments in key technologies such as IoT, big data, AI and robotics. The government has launched various initiatives to support the development and integration of these technologies with traditional industries, with the aim of building a sustainable and innovative smart economy. These technologies play a critical role in China's industrial upgrading and transformation, and their continued development and adoption are expected to shape the future of China's economy and global competitiveness.